Territoriality and time budget of breeding Coots - Salath, Tobias; Boy, Vincent (Wildfowl, 1987)
The time budget of breeding Coot Fulica atra was studied in the Camargue, southern France. The amount of time Coot spent feeding was highest during the pre-laying period, and declined after egg-laying. Females spent about half as much time again feeding during the pre-laying period as did males, and this was probably related to clutch formation. During the same period males spent more time in territorial advertisement and territorial defence. Incubation and feeding of young was shared equally by the sexes. Variability in resources in the marsh habitat probably forced Coot to compete for good territories. Thus territorial behaviour during the pre-laying period occupied up to 16% of the time budget. The allocation of time by Coots was very similar to that of its American allospecies Fulica americana.